The main consumer properties of electric vehicle charging services at power charging stations in regions of the North-Caucasian Federal District - V. A. Zavolokin (Вестник Северо-Кавказского федерального университета)
Introduction. The research of the main consumer properties of services of charging of electric vehicles at power charging plants is represented urgent as lays the theoretical foundation for their development.Goal. A research of the main consumer properties of services of charging of electric vehicles at power charging plants in regions of the North-Caucasian Federal District.Materials and methods. Data for a research were collected manually with use of information resources of service providers of charging, and also third-party information resources. The research used observation, comparison, comparison, abstraction, systematization, analysis and other methods.Results and discussion. It has been specified that the main consumer properties of charging service of electric vehicles at charging stations for buyers are the location and load of charging stations, types of charging stations on capacities, types of connectors, service prices of charging stations, existence of the Internet, need of use of special skills by users. The location of the charging station is its key consumer property. The research showed that at charging stations of North-Caucasian Federal District the price is established by operators in the range from 9 to 20 rubles per kW*h. In North-Caucasian Federal District, the lack of the Internet in certain territories can interfere with effective operation of charging stations by users. Specific knowledge and skills are necessary for owners of electric vehicles to use the charging stations.Сonclusion. The understanding of the revealed consumer properties of the studied services allows networks of charging stations to form and develop competitive business in the market of services of charging of electric vehicles, and also in several adjacent markets which accompany them.